1974
DOI: 10.1002/aic.690200517
|View full text |Cite
|
Sign up to set email alerts
|

Models of secondary nucleation attributable to crystal‐crystallizer and crystal‐crystal collisions

Abstract: Collisions and Crystal-Crysta IThe rate of secondary nucleation of ice, assumed to be proportional to the product of collision frequency and impact energy, has been quantitatively modeled using idealized representations of collisions between crystals and either other crystals or surfaces in the crystallizer. The crystal-crystallizer collisions were assumed to be driven by either steady or turbulent fluid motion and the crystal-crystal collisions were assumed to be driven by either gravitational forces or turbu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
1

Year Published

1976
1976
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 5 publications
0
44
0
1
Order By: Relevance
“…B" is predicted independent of impeller RPM (as found in this study), since collision frequency does not limit the formation of nuclei, The observed proportionality between B" and M T would also be expected because the number of dendritic sites depends on the amount of crystals present in suspension. The growth limited nucleation proposed by Wang and Estrin is in direct contrast to removal limited nucleation model proposed by Evans et al (1974). The latter formulation predicts B" to be strongly influenced by the agitation level as found in the study of potassium sulfate .…”
Section: Constablementioning
confidence: 82%
See 1 more Smart Citation
“…B" is predicted independent of impeller RPM (as found in this study), since collision frequency does not limit the formation of nuclei, The observed proportionality between B" and M T would also be expected because the number of dendritic sites depends on the amount of crystals present in suspension. The growth limited nucleation proposed by Wang and Estrin is in direct contrast to removal limited nucleation model proposed by Evans et al (1974). The latter formulation predicts B" to be strongly influenced by the agitation level as found in the study of potassium sulfate .…”
Section: Constablementioning
confidence: 82%
“…Bennet, Fiedelman, and Randolph (1973) ; Ottens and de Jong (1973) ;and Evans, Sarofim, and Margolis (1974) derive similar power-law expressions using a semiempirical approach. If the growth rate of crystals is size independent, the following power-law model can be used to express its dependence on supersaturation G = k , .…”
mentioning
confidence: 92%
“…For example, herein, a secondary nucleation model based upon the work of Ref. 29 was used to describe the nucleation effect due to attrition. And for crystal agglomeration effect, the A 50 parameter was introduced to represent the combined effect of material strength, point of contact between two crystals and vessel geometry.…”
Section: Flowsheet Models Of Periodic Flow Crystallization Processmentioning
confidence: 99%
“…At this stage, the limiting step is the removal of nuclei from the surface of the existing crystals after each collision or unit of abrasion (Evans et al, 1974a). Higher agitation promoted both crystalcrystallizer and crystalecrystal collisions (Evans, Sarofim, & Margolis, 1974b), leading to higher collision frequency and Fig. 7.…”
Section: Analysis Of Spectroscopy Datamentioning
confidence: 99%